Social Prescription - Madhur Verma; Sourabh Sharma; Nitin Kapoor; Sanjay Kalra (Journal of the Pakistan Medical Association, 2026)
Social prescription is a person-centred approach that links individuals to non-medical, community-based resources through trained “social prescribers.” This model complements medical therapy by providing psychosocial support, peer engagement, lifestyle guidance, and assistance in navigating local resources. Social prescription promotes self-efficacy, adherence to lifestyle interventions, and psychological well-being by facilitating peer support, practical problem-solving, and spiritual or cultural engagement. The South Asian setting is particularly well suited for social prescription due to its traditionally strong community networks. Despite its promise, implementation is challenged by the lack of formal frameworks, standardized training, and structured collaboration between healthcare and social care sectors. This article discusses the concept, relevance, benefits, challenges, and opportunities of social prescription and proposes a structured approach for its integration into chronic disease care pathways. Keywords: Biopsychosocial, community health, person centred care, social